2006
DOI: 10.1007/s10562-006-0026-x
|View full text |Cite
|
Sign up to set email alerts
|

Ni–Fe Catalysts Based on Perovskite-type Oxides for Dry Reforming of Methane to Syngas

Abstract: LaNi (1)x) Fe x O 3 (x=0, 0.2, 0.4 and 0.7) perovskite-type catalysts were modified by the partial substitution of nickel by iron, aiming to increase the stability and resistance to carbon deposition during the methane dry reforming reaction. The results showed that a suitable combination of precipitation and calcination steps could result in oxides with the desired structure and with improved properties from the point of view of heterogeneous catalysis. The partial substitution of Ni by Fe in the perovskite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 17 publications
2
43
1
Order By: Relevance
“…In case of reduced LaNi0.8Fe0.2O3 catalyst; however, the H2:CO product ratio was close to 0.5, which was a consequence of the RWGS reaction over DRM reaction at 650 °C. This is explained due to the fact that the presence of Fe in the Ni metal particles favored the RWGS reaction [43], whereas exsolution from LaNi0.8Mn0.2O3 produced only pure Ni nanoparticles.…”
Section: Catalytic Activity For Dry Reforming Of Methane (Drm)mentioning
confidence: 99%
“…In case of reduced LaNi0.8Fe0.2O3 catalyst; however, the H2:CO product ratio was close to 0.5, which was a consequence of the RWGS reaction over DRM reaction at 650 °C. This is explained due to the fact that the presence of Fe in the Ni metal particles favored the RWGS reaction [43], whereas exsolution from LaNi0.8Mn0.2O3 produced only pure Ni nanoparticles.…”
Section: Catalytic Activity For Dry Reforming Of Methane (Drm)mentioning
confidence: 99%
“…The presence of this peak indicates the interaction between Ni and Fe to form bimetallic particles which is also in agreement with the XRD result. Literature studies have concluded that for catalysts that contain Ni, Fe and La, a fraction of the Fe undergoes reduction with the aid of Ni and Ni-Fe bimetallic particles are formed after the reduction process [44][45][46][47][48][49].…”
Section: Xrd -Structural Analysismentioning
confidence: 99%
“…However, substitution of Ni by low contents of Fe (i.e. Ni-Fe catalysts) promotes more stable catalysts [4].…”
Section: Ch4 + Co2 ↔ 2h2 + 2co (1)mentioning
confidence: 99%